THE USE OF MALAYSIAN MODEL OF PICTORIAL VOCABULARY FOR VIRTUAL LEARNING AMONG LOWER SECONDARY ESL STUDENTS IN MALAYSIA - Mohd Tahir, Mohd Haniff (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Vocabulary learning is only indirectly integrated into the four core skills of the Standards-Based English Language Curriculum (SBELC): reading, writing, listening, and speaking. English as a Second Language (ESL) students with limited vocabulary knowledge often face difficulties to learn and use English on a regular basis. In a sustainable Open Distance Learning (ODL), this study uses Malaysian model of pictorial vocabulary to help students learn vocabulary remotely. In this study, 300 ESL students from lower secondary schools across Malaysia use this model to help them learn the target words mentioned in the SBELC. A mixed methods research design is employed. After using the model, students have answered an evaluation form which is evaluated descriptively in terms of its mean scores and standard deviation. The qualitative data from the interview with the students are transcribed, categorised, and coded using content analysis. Based on the research findings, the students’ vocabulary knowledge has substantially increased after using the model. This study's implications indicate that the use of the Malaysian model of pictorial vocabulary learning is both interactive and effective in learning the target words. In the area of vocabulary acquisition, this research adds value as it can be used to carry out additional research to enhance the ability of students to learn new words.